Study on phytotoxicity evaluation and physiological properties of nicosulfuron on sugar beet (Beta vulgaris L.) - Wang, Longfeng; Riaz, Muhammad; Song, Baiquan; Song, Xin; Huang, Wengong; Bai, Xiaoshan; Zhao, Xiaoyu (Frontiers in Plant Science, 2022)
Nicosulfuron is an herbicide widely used in corn fields. In northeast China, sugar beet is often planted adjacent to corn, resulting in frequent phytotoxicity of nicosulfuron drift in sugar beet fields. This study was conducted by spraying nicosulfuron to assess the phytotoxicity and clarify the mechanism of nicosulfuron toxicity on sugar beet. The results showed that nicosulfuron impaired growth and development by reducing photosynthetic capacity and disrupting antioxidant systems at a lethal dose of 81.83 g a.i. ha–1. Nicosulfuron damaged the structure and function of photosynthetic system II (PSII), lowered photosynthetic pigment content, and inhibited photosynthetic efficiency. Compared with the control, the electron transfer of PSII was blocked. The ability of PSII reaction centers to capture and utilize light energy was reduced, resulting in a weakened photosynthetic capacity. The maximum net photosynthetic rate (Amax), light saturation point (LSP), and apparent quantum yield (AQY) decreased gradually as the nicosulfuron dose increased, whereas the light compensation point (LCP) and dark respiration (Rd) increased. Nicosulfuron led to reactive oxygen species (ROS) accumulation in sugar beet leaf, a significant rise in malondialdehyde (MDA) content, electrolytic leakage (EL), and considerable oxidative damage to the antioxidant system. This study is beneficial for elucidating the effects of nicosulfuron toxicity on sugar beet, in terms of phytotoxicity, photosynthetic physiology, and other mechanisms.